Designable Micro‐/Nano‐Structured Smart Polymeric Materials. Issue 46 (10th March 2022) - Wang, Wei; Li, Ping‐Fan; Xie, Rui; Ju, Xiao‐Jie; Liu, Zhuang; Chu, Liang‐Yin
Abstract: Smart polymeric materials with dynamically tunable physico‐chemical characteristics in response to changes of environmental stimuli, have received considerable attention in myriad fields. The diverse combination of their micro‐/nano‐structural and molecular designs creates promising and exciting opportunities for exploiting advanced smart polymeric materials. Engineering micro‐/nano‐structures into smart polymeric materials with elaborate molecular design enables intricate coordination between their structures and molecular‐level response to cooperatively realize smart functions for practical applications. In this review, recent progresses of smart polymeric materials that combine micro‐/nano‐structures and molecular design to achieve designed advanced functions are highlighted. Smart hydrogels, gating membranes, gratings, milli‐particles, micro‐particles and microvalves are employed as typical examples to introduce their design and fabrication strategies. Meanwhile, the key roles of interplay between their micro‐/nano‐structures and responsive properties to realize the desired functions for their applications are emphasized. Finally, perspectives on the current challenges and opportunities of micro‐/nano‐structured smart polymeric materials for their future development are presented. Abstract : Smart polymeric materials with elaborate micro‐/nano‐structural and molecular designs to achieve designed functions for myriad applications are summarized. The smart materials, including responsive hydrogels, gating membranes, gratings, milli‐particles, micro‐particles and microvalves, can achieve intricate coordination between their micro‐/nano‐structures and responsive properties to cooperatively achieve desired functions.